Developing good practice in children's services - Harris, John, 1952-; White, Vicky, 1959- (J. Kingsley Publishers, 2004)
This book is concerned with how social workers and managers can engage reflectively and proactively with changes in children's services. Vicky White and John Harris have drawn together the contributors' experiences of working with children in a broad range of settings, emphasising ways in which the current context of change can be used as an opportunity to enhance the quality of service provision and achieve better outcomes for children and their families. The authors examine approaches to the assessment of children in need and the analysis of risk, and consider the impact of poverty and socia.